The Maritime Food Processing Industry: A Comparison of the Competitive Characteristics of Low and High Value Added Firms - Brown, Mark William (My University, 1994)
The Maritime provinces have been historically characterized as primarily low value added resource producing economies. One of the sectors identified most with this economy is food processing, which accounts for a quarter of the region's manufacturing output. Among the problems facing the Maritime economy has been an inability to add value to the region's natural resource output. This has left the economy reliant on commodity production which, in the long run, is vulnerable to outside competition.
The region has also been economically depressed compared to other parts of Canada. Many initiatives have been undertaken to reduce disparities of income and employment, but by and large they have been unsuccessful. Some have argued for a shift in regional development policy away from incentives to attract new industry and towards the development of local industry. One possible form this development might take is increased value added to the region's resource production. It was hypothesized in the thesis that there are obstacles to higher value added production which follow from the more sophisticated competitive requirements of higher value added firms.
To determine the degree of value added production and the characteristics of higher value added firms, a mail survey was sent to the population of food processors in the region. Based on the results of the survey it was found that higher value added firms rely on often more advanced factors and strategies to establish and maintain their competitiveness. Although there are many firms in the region producing higher value added products, these firms do not have significantly higher growth rates than lower value added firms. This can, in part, be explained by weaknesses in the region's ability to provide the factors and incentives which higher value added firms rely upon to be successful.
It was also concluded from the study that if it is the goal of regional development policy to encourage higher value added production, development efforts should be broader in focus. In other words, policies cannot be based primarily on direct incentives to business.
Keywords: Geography; Geography